Keith Urban - Apter, Jeff (2023)
"In the first and only definitive biography of country music star Keith Urban, insider Jeff Apter chronicles how a skinny, shy high school dropout with an outrageous mullet went from humble origins in Australia to conquering Nashville and global stardom plus his struggles with addiction, marriage to Nicole Kidman, turns on American Idol, and more."--Publisher.